Of pipe dreams and fossil fools: Advancing Canadian fossil fuel hegemony through the Trans Mountain pipeline. (November 2020) - Kraushaar-Friesen, Naima; Busch, Henner
Abstract: This article uses the Trans Mountain pipeline expansion project as a Canadian case study to critically examine and showcase one instance of the hegemony of fossil fuels in the era of global heating. The present Canadian federal government, under the leadership of Liberal Prime Minister Justin Trudeau, is seeking to simultaneously position itself as a global climate leader while supporting the exploitation of Canada's extensive bitumen oil reserves. We apply a critical discourse analysis to seven speeches given between 2016 and 2019 by two members of the Canadian federal government on the Trans Mountain pipeline expansion project to interrogate how the government discursively reconciles these two contradicting stances. Our analysis yields three main results: 1) the government naturalizes bitumen as a substance, culturally and politically hindering the capacity for Canada to move beyond it, 2) the extraction of bitumen is portrayed as an imperative, implicating the overall economic and social health of Canada and justifying the government's use of coercion and 3) appeals to climate change and action are paradoxically subsumed into the argument for bitumen extraction. Overall, we argue, this discourse depoliticizes the social and environmental struggles surrounding bitumen extraction. It functions to maintain the hegemony of fossil fuels in the era of global heating, thus foreclosing on possibilities of leaving the fuels in the ground while reinforcing Canadian bitumen's multi-dimensional carbon lock-in.